Nature and conduct / edited by R.S.Peters - "Peters, R.S.( ed.)" (London, 1975)
This book is divided into four sections. The first deals with general questions about the nature of man and the relevance for conduct of answers to such questions. The second deals with ways in which specific aspects of human nature such as conscience, needs, happiness and role-paying are related to human conduct. In the third section the general question of man's relationship to the natural world is discussed. The final section is concerned with the ethics of environmental planning. I
Keywords: Philosophy